NAVIGATING THE STAGES OF CULTURE SHOCK: ASIAN ERASMUS+ STUDENTS’ EXPERIENCES OF STUDYING ABROAD IN EUROPE - Rizqi Kurniawan Tribowo; Joe Harrianto Setiawan (Bajang Institute, 2026)
International student mobility has become a central feature of higher education internationalization, offering opportunities for intercultural learning while also exposing students to cultural challenges. This study explores how Asian Erasmus+ students experience and navigate culture shock during their study abroad experience in Europe. Employing a qualitative descriptive approach, the research draws on in-depth interviews with Asian exchange students who participated in Erasmus+ mobility programs across various European host countries. Data were analyzed thematically using a stages of culture shock framework, encompassing honeymoon, disintegration, reintegration, adjustment, and adaptation. The findings reveal that culture shock among Asian Erasmus+ students unfolds as a dynamic and non-linear process rather than a fixed sequence of stages. Initial enthusiasm and idealized expectations during the honeymoon stage gradually give way to confusion related to academic autonomy, communication norms, and everyday social practices. This is followed by cultural frustration and identity negotiation, as students critically compare host and home cultures. Over time, participants develop coping strategies that support adjustment and autonomy, leading to functional adaptation and intercultural competence. Importantly, adaptation is found to be context-dependent and pragmatic, reflecting the time-limited nature of short-term exchange programs rather than complete cultural assimilation. This study contributes to intercultural communication and international education literature by reaffirming the relevance of the culture shock framework while highlighting its flexibility in short-term mobility contexts. The findings underscore the need for stage-sensitive institutional support and culturally responsive academic practices to enhance international students’ study abroad experiences. The study offers practical implications for universities and mobility program coordinators seeking to foster inclusive and supportive international learning environments